The relationship between environmental efficiency and manufacturing firm's growth - Massimiliano Mazzanti; Giulio Cainelli; Roberto Zoboli (Fondazione Eni Enrico Mattei (FEEM), 2008)
This paper investigates the empirical link between emission intensity and economic growth, using a very large data set of 61,219 Italian manufacturing firms over the period 2000-2004. As a measure of lagged environmental performance (efficiency) at firm level we exploit NAMEA sector for CO2, NOx, SOx data over 1990-1999. The paper tests the extent to which (past) environmental efficiency/intensity, which is driven by structural features and firm strategic actions, including responses to policies, influences firms growth. Our results show, first, a typical trade off generally appearing for the three core environmental emissions we analyse: lower environmentally efficiency in the recent past allows higher degrees of freedom to firms and relax the constraints for growth, at least in this short/medium term scenario. Nevertheless, the size of the estimated coefficients is not large. Trade offs are significant for two emission indicators out of two, but quite negligible in terms of impacts, besides the case of CO2. For example, growth is reduced by far less than 0.1% in association to a 1% increase of environmental efficiency. In addition, non-linearity seems to characterise the economic growth-environmental performance relationship. Signals of inverted U shape appear: this may be a signal that both firm strategies and recent policy efforts are affecting the dynamic relationship between environmental efficiency and economic productivity, turning it from an usual trade off to a possible joint complementary/co-dynamics.
Keywords: C23; D21; O32; Q55; 330; Firm Growth; Manufacturing; Emission Intensity; Economic Performance; Environmental Performance